2023
DOI: 10.1177/17590914231214116
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam Binding Inhibitor Control of Eu- and Hypoglycemic Patterns of Ventromedial Hypothalamic Nucleus Glucose-Regulatory Signaling

Sagor C. Roy,
Subash Sapkota,
Madhu Babu Pasula
et al.

Abstract: Pharmacological stimulation/antagonism of astrocyte glio-peptide octadecaneuropeptide signaling alters ventromedial hypothalamic nucleus (VMN) counterregulatory γ-aminobutyric acid (GABA) and nitric oxide transmission. The current research used newly developed capillary zone electrophoresis-mass spectrometry methods to investigate hypoglycemia effects on VMN octadecaneuropeptide content, along with gene knockdown tools to determine if octadecaneuropeptide signaling regulates these transmitters during eu- and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…These data suggest that, changes of energy status that lead to elevated circulating insulin levels can favour the increase of DBI transcription. 47 , and our study furthers these observations by demonstrating the insulin evokes release of DBI from astrocytes within the NTS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These data suggest that, changes of energy status that lead to elevated circulating insulin levels can favour the increase of DBI transcription. 47 , and our study furthers these observations by demonstrating the insulin evokes release of DBI from astrocytes within the NTS.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, a study in 2013 demonstrated that injecting ODN into the hypothalamus could improve glucose tolerance, though the precise mechanism remained unclear 32 . Remarkably, intraperitoneal injection of insulin elicits an upregulation of DBI mRNA expression in the ventromedial hypothalamus 47 , and glucose infusion in fasted rats leads to an elevation in DBI mRNA levels within the hypothalamus 32 . Conversely, fasting has been shown to decrease DBI mRNA levels in the hypothalamus 46 .…”
Section: Discussionmentioning
confidence: 99%